Walking duration in daily travel: an analysis among males and females using a hazard-based model. Issue 4 (10th December 2021) - Saeidi Hosseini, Seyed Ahmad Reza; Hatamzadeh, Yaser
Abstract : This study examines how various travel/built environmental and individual/household characteristics influence the walking durations of males and females in the city of Rasht, Iran, using data from the 2007 Rasht Household Travel Survey (RHTS). Accelerated hazard (AH) modelling, as a new approach in walking-related studies, was used to predict walking durations. The survival curve analysis showed that the ideal walking time was five minutes, but walking up to ten minutes was also acceptable. The AH models indicated that the walking duration of males and females varied under different conditions and contexts. For example, female workers were likely to walk longer trips relative to non-workers; however, this was the opposite among males. Household characteristics such as car ownership were found with greater negative effect on walking duration of males than females. Furthermore, zones with higher land use mix and higher connectivity led to shorter walking duration in both models.